Eco-Friendly Management of Rice Diseases - Razu, Md. Amanut Ullah; Hossain, Ismail (International Journal of Applied Sciences and Biotechnology, 2015)
Comparative efficacy of BAU-Biofungicide (2%), a product of Trichoderma harzianum, Garlic (Allium sativum) clove extract (5%), Allamanda(Allamanda cathartica) leaf extract (5%), Bion (25ppm), Amistar (0.1%) and Tilt 250EC (0.1%) were evaluated for eco-friendly managementof diseases of rice cv. BRRI Dhan-49 under field and laboratory conditions from July,2013 to March,2014. The field experiment was carriedout following Randomised Complete Block Design and the laboratory experiments were done following Completely Randomized Design.Brown spot, Narrow brown leaf spot, Bacterial leaf blight and Sheath blight were recorded in the field. The lowest incidence of brown spotand narrow brown leaf spot was observed in plots treated with BAU-Biofungicide and that of bacterial leaf blight was observed in plots sprayedwith Allamanda leaf extract. In case of sheath blight, the lowest incidence was observed in BAU-Biofungicide sprayed plots. The highest grainyield (3680.34kg/ha) was recorded in plots sprayed with BAU-Biofungicide which is 40.56% higher over control. The highest seed germination(%) was recorded when seeds were treated with Garlic clove extract (89.29%) followed by BAU-Biofungicide (87.30%). The prevalence ofseed-borne fungi was investigated by blotter method. The identified seed-borne fungal species were Bipolaris oryzae, Fusarium oxysporum,Fusarium moniliforme, Curvularia lunata, Aspergillus niger and Aspergillus flavus. Maximum reduction of seed-borne infection of pathogenswas obtained by treating seeds with BAU-Biofungicide (2% of seed weight). DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11977 Int J Appl Sci Biotechnol, Vol. 3(1): 80-88